PENGENALAN AKSES KE PERBANKAN SYARIAH MELALUI EDUKASI HIDROPONIK DAN AQUAPONIK UNTUK MASYARAKAT PERKOTAAN DI DESA CINTAMANIK, KECAMATAN CIGUDEG, KABUPATEN BOGOR - Irpan Maulana; Rully Trihantana; Ria Kusumaningrum (SAHID DEVELOPMENT JOURNAL, 2021)
Abstract Indonesia is one of countries affected by the pandemic of Covid-19. All aspects of prevention and countermeasures have been carried out by various parties around the world regarding the pandemic that has occurred from March 2020 to the present. The agricultural sector is of concern because it has an important role and is closely related to national food security, as well as the supporting sector tostrengthen Indonesia economy, particularly in such condition. Agriculture also can offer a solution to avoid food crises. One of the activities is to diversify food and not rely entirely on the amount of food in the market. This activity attempts to utilized limited area available in the city, thus it becomes more productive especially during pandemic. The hydroponic and aquaponic system of agricultural cultivation technology provides an alternative to be used as an adequate source of income and can meet family food needs. This technique can be carried out by people who live both in rural and urban areas which is not required a wide space. This activity can strengthen family food security as well asn become additional income or even the main income of the family. Keywords: aquaponic, food security hidroponic